TRÊS AUTORES, TRÊS TEMPOS: O ENSINO DE ARITMÉTICA, À LUZ DO MÉTODO DE DECROLY - Lemes, Ana Maria Ferreira (2022)
With the purpose of answering the following guiding question: To which extent three authors in three times, appropriate, in their works of the Interest Centers Method for the teaching of Arithmetic? Objectives: To identify and to analyze, in three Pedagogical Manuals – Omer Buyse’s (1927), Everardo Backheuser’s (1946) and D’Ávila’s (1965), the three phases – observation, association and expression – of the Interest Centers Method, preconized by Jean-Ovide Decroly, specially, related to the Arithmetic; To Understand the Decroly’s ideas appropriations, realized by the aforementioned authors; To analyze the presence of the Interest Centers relative to the teaching of Arithmetic in the aforementioned Pedagogical Manuals. It is a qualitative research with a historic-documental characteristic, based in the Cultural History constructs, mainly from Roger Chartier in what is referent to the representation, practice and appropriation, and from Michel De Certeau in what links to the strategies and tactics. Concludes that the Decroly’s Interest Centers appropriations were concerning to the three phases and the six decrolyan axes, and in general, more specifically to the Arithmetic, which was worked out based in concrete and globalized teaching, inserted in the student’s daily matters, bringing them as the center of such movement.